New taxa of quill mites (Acari: Cheyletoidea: Syringophilidae) - Skoracki, Maciej; Oconnor, Barry (Zootaxa, 2010)
Four new genera and eight new species are described: Apodisyringophilus collocalius gen. nov., sp. nov. from Collocalia esculenta (Linnaeus) (Apodiformes: Apodidae) from the Philippines, Bochkovia phalaropi gen. nov., sp. nov. from Phalaropus fulicarius (Linnaeus) (Charadriiformes: Scolopacidae) from the USA, Ciconichenophilus phoeniconaias gen. nov., sp. nov. and Stibarokris phoeniconaias sp. nov. from Phoeniconaias minor (Geoffroy Saint-Hilaire) (Phoenicopteriformes: Phoenicopteridae) from Botswana, Picisyringophilus kratos gen. nov., sp. nov. from Picoides pubescens (Linnaeus) (Piciformes: Picidae) from the USA, Charadriiphilus re sp. nov. and Picobia pteroclesi sp. nov. from Pterocles senegallus (Linnaeus) (Pteroclidiformes: Pteroclididae) from Egypt, and Neoaulonastus chrysocolaptes sp. nov. from Chrysocolaptes lucidus (Scopoli) (Piciformes: Picidae) from the Philippines. The new genera differ from the closely related genera by the following characters: Apodisyringophilus gen. nov. differs from Syringophiloidus Kethley by the absence of leg setae lGIV, the presence of the short hysteronotal setae and by apodemes I fused to apodemes II; Bochkovia gen. nov. differs from Procellariisyringophilus Schmidt et Skoracki by the presence of the dentate cheliceral stylets and two pairs of pseudanal setae, the absence of setae vsI and by the presence of the strongly curved claws on tarsi I-IV; Ciconichenophilus gen. nov. differs from Chenophila Kethley by the stylophore rounded posteriorly, the long hysteronotal setae, apodemes I not fused to apodemes II and by the absence of leg setae vsII; Picisyringophilus gen. nov. differs from Mironovia Chirov et Kravtsova by coxal fields I and II subequal in sizes and by setae se situated distinctly anterior to setae c1. Data on distribution of all known syringophilid genera on host families and orders are provided.